From Fragments to Form. Multidisciplinary Approaches to the Reconstruction of Past Works of Art - Piccione, Caterina; Argentina, Marco (2025)
This volume investigates the reconstruction of past works of art as a philologically grounded endeavor. Exploring the passage from fragment to form, it moves from partial traces to a perspective that sheds light on earlier artistic practices — the aim is not totality, but a careful understanding of cultural heritage, though marked by gaps and transformations. Contributions from diverse disciplines resonate with one another, revealing shared challenges and methodological affinities. Far from nostalgia, the essays show how reconstruction illuminates both past and present, fostering a meaningful dialogue with History.